Economic Recovery in the Age of COVID-19 - Carlos Cuerpo (Intereconomics)
Abstract Economic recovery post-COVID-19 will be structured around answering a number of fundamental questions. It is necessary to take stock of the extent of the recovery and of the transformation our economies have experienced in the last year and a half.